Retrospectroscope exploding glass eyes. - Geddes, L.A.
Injury to the eye often necessitates removal of the eye (enucleation). The development of the glass eye is discussed and the fact that hollow-glass eyes "exploded" spontaneously. Two explanations for glass-eye "explosions" were popular: (1) the glass became eroded by tissue fluids in the socket and (2) excess pressure produced the "explosion." The accounts presented provide the evidence.
Keywords: Accident; Excess pressure; Exploding glass eyes; Eye injury; Glass-eye breakage; Implosion